Selection of indigenous Saccharomyces cerevisiae strains to ferment red musts at low temperature - Massera, Ariel Fernando (2012)
The aim of this work was to select native Saccharomyces cerevisiae strains to conduct the alcoholic fermentation of red must at low temperature (15°C), thus producing volatile compounds that enhance the aromatic profile of young red wines. Native yeast strains were isolated from red musts and characterized using different oenological and technological criteria. The selection procedure included evaluating the yeasts’ characteristics in order to efficiently transform grape sugars into alcohol and carbon dioxide at a controlled rate and without development of off-flavors. The selection procedure also considered another set of oenological properties, namely: SO2 resistance, killer activity, low foam production, volatile acidity, high ethanol production and tolerance, sugar exhaustion, growth at low temperature, growth at high sugar concentration, formation of H2S, β-glycosidase activity and volatile compound synthesis in synthetic media. The pre-selected native S. cerevisiae strains were evaluated in microvinifications of Malbec must at 15°C, which were then evaluated to volatile compound composition and subjected to a sensorial descriptive analysis. The complete selection procedure was carried out over 2 years. This study provides a complete description of techniques for obtaining validated scientific results that can be used by oenologists and researchers in the selection of specific yeasts.